PENGARUH TINGKAT MARGIN TERHADAP KEPUTUSAN PENGAMBILAN PEMBIAYAAN MURABAHAH DI BMT UGT SIDOGIRI CABANG WARU SIDOARJO - Aisyah Nur Aini (El-Qist: Journal of Islamic Economics and Business (JIEB), 2015)
The research was titled â€œPengaruh Tingkat Margin Terhadap Keputusan Pengambilan Pembiayaan MurÄbahah di BMT UGT Sidogiri Cabang Waru Sidoarjoâ€ is a a quantitative research to answer the questions whether the margin influence on customerâ€™s decision-making margin murabaha financing and the extent of influence on the decisions-making murabaha financing at BMT UGT Sidogiri Waru Sidoarjo. This research uses a purposive sampling method with a sample of 90 customers who take murabaha financing. Questionnaires were tested for validity and reliability of the 20 customers prior to the collection of research data. Test equipment used in this research is to use analysis prerequisite test including normality test and test heteroskedastisitas. For data analysis used a simple linear regression analysis. The analysis of this study concluded that the level of margin positive and significant impact on the decision-making Murabaha financing as indicated by the value of the correlation coefficient (R) of 0.989, the coefficient of determination (R2) of 0.977.